Construction of thermo-tolerant yeast based on an artificial protein quality control system (APQC) to improve the production of bio-ethanol. (23rd February 2018) - Xu, Ke; Yu, Liping; Bai, Wenxin; Xiao, Bing; Liu, Yueqin; Lv, Bo; Li, Jun; Li, Chun
Highlights: APQC for improving the thermo-tolerance of industrial yeast. The proteastasis has been effectively improved under high temperature. Ethanol yield of thermo-tolerant engineered yeast were improved. Abstract: A major challenge for the production of bio-ethanol is to develop yeast that can sustain growth under high temperature. Here, we show the application of an artificial protein quality control (APQC) system to an industrial Saccharomyces cerevisiae strain for improving thermo-tolerance, a key trait for a bio-ethanol fermentation program. All engineered strains exhibited a significantly higher growth rate and cell viability at 37 °C, which conferred increased thermo-tolerance and more efficient glucose conversion to ethanol. Furthermore, the analysis of ubiquitination and the enzyme activities of pyruvate kinase (PK) and malate dehydrogenase (MDH) indicated strengthened protein quality, implying that proteostasis had been effectively improved at higher temperature. Industrial material fermentation results from yeast-RSP5-UBC4 (combined expression of ubiquitin conjugated enzyme E2 and ubiquitin ligase E3) showed a 2.4% increase in ethanol production. All these findings prove that APQC is suitable for improving yeast resistance to high temperature during industrial bio-ethanol production.